Making Room for Reason: Hegel, Kant, and the Corpse of Faith and Knowledge - Jensen, Kipton E. (Philosophy & theology, 2000)
The following essay aims at a revisionist reading of Hegel’s “Faith and Knowledge.” Whereas Kant found it necessary to limit [aufheben] reason in order to make room for faith, a principle adopted though significantly revised by Jacobi (and Schleiermacher) and Fichte, Hegel reverses this religious dictum. Ostensibly critical of the theological truce of the times, between a brand of reason no longer worthy of the name and a faith no longer worth the bother, Hegel’s 1802 essay constitutes his first sustained effort to reflect himself out of—or beyond—the limits of reflectivity itself.